Analysis of Mobile Credit Semester (KRS) Using Emotion Sampling Device (ESD) - Nabillah Annisa Rahmayanti; Wahyu Andhyka Kusuma (Universitas Islam Sultan Agung, 2018)
Emotion Sampling Device (ESD) is a method used to evaluate the effects of a digital product such as an existing system on a smartphone against the user's emotions. Sometimes when we use a system we unconsciously give an emotion to it. The emotions of each user are divided into some common emotions such as happy, sad, shocked, scared, angry and uninterested. Using this method, the researcher aims to analyze the user's emotion against prototype or KRS Mobile design with KRS case study that exist in University of Muhammadiyah Malang. With a new and different look from KRS that existed previously at the University of Muhammadiyah Malang allows its users to give their own emotions to the prototype. In analyzing emotions, researchers adapted a toeri from the psychological side of Appraisal Theory to obtain data from questionnaires on respondents. The result of this research is the percentage of emotion from each respondent that will be made proving that the prototype is feasible or not to be applied.Keywords: Emotion Sampling Device, KRS Mobile, Prototype, Appraisal Theory